BRAND PREFERENCE, SEGMENTATIONS AND THE IMPLICATIONS ON THE CUSTOMER OF ISLAMIC BANKS IN RURAL AREAS (Journal of Economics and Sustainability, 2019)
Although the assets of Islamic banks are continuously growing, the proportion of their market share remains stagnant. To date, a few studies on consumer behaviour have investigated the products offered by Islamic banks in Indonesia. Therefore, the purpose of this study was twofold: firstly, it determined the influence of environmental, cultural, personal and psychological factors on choosing Sharia-financing products; secondly, it assessed the role of demographic factors in influencing the choice of Sharia-financing products. The population of the study was Moslem consumers of Islamic banks operating in Banyumas Central Java Indonesia. The method used to test the hypothesised relationships was logistic regression analysis. The result of the study revealed that culture, socio-environmental conditions, personality, and psychological factors influenced Moslem consumers in choosing Sharia- financing products. No demographic differences were found in choosing Sharia-financing products. The result of the study guides Islamic financial institutions in determining the strategy for their future growth. Specifically, Islamic banks need to pay attention to various aspects of the culture.